2020
DOI: 10.3390/ijms21082973
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the Diffuse Noxious Inhibitory Controls in Chronic Joint Inflammatory Pain Is Accompanied by Anxiodepressive-Like Behaviors and Impairment of the Descending Noradrenergic Modulation

Abstract: The noradrenergic system is paramount for controlling pain and emotions. We aimed at understanding the descending noradrenergic modulatory mechanisms in joint inflammatory pain and its correlation with the diffuse noxious inhibitory controls (DNICs) and with the onset of anxiodepressive behaviours. In the complete Freund's adjuvant rat model of Monoarthritis, nociceptive behaviors, DNICs, and anxiodepressive-like behaviors were evaluated. Spinal alpha2-adrenergic receptors (a2-AR), dopamine beta-hydroxylase (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 65 publications
(147 reference statements)
1
18
0
Order By: Relevance
“…This was consistent with previous results that patients with whiplash injury report higher pain scores and larger areas of local and referred pain than healthy controls [35]. The increased clinical pain observed in the wTMD group may be due to impaired diffuse noxious inhibitory controls (DNICs), a measure of central nervous system pain inhibition [36]. Moreover, sleep disturbance is related to decreased DNICs in patients with TMD [37].…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with previous results that patients with whiplash injury report higher pain scores and larger areas of local and referred pain than healthy controls [35]. The increased clinical pain observed in the wTMD group may be due to impaired diffuse noxious inhibitory controls (DNICs), a measure of central nervous system pain inhibition [36]. Moreover, sleep disturbance is related to decreased DNICs in patients with TMD [37].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, previous research has demonstrated abolished DNIC expression in the late stage of a model of chronic joint inflammatory pain and impaired descending noradrenergic modulation with relation to the LC. 24 This insight, specifically linking stage-specific DNIC attenuation to impaired LC functionality, lends weight to the argument that communication between LC and DNIC origin nuclei governs the final output of descending modulatory controls that are subserved by noradrenaline. However, the nature of the influence is unknown, and a future research goal includes employing genetic strategies to determine the nature of the neuronal populations that mediate crosstalk between the LC and DNIC origin nuclei.…”
Section: Discussionmentioning
confidence: 92%
“…This of course does not exclude a role for the A6, where activity therein seemingly alters higher brain centres in concert. Insight regarding brainstem and spinal α 2 -AR-mediated mechanisms, specifically linking DNIC attenuation to impairment of descending noradrenergic modulation from the A6 in a rodent model of joint inflammatory pain 53 , highlights the need to investigate governance of effects subsequent to A-nucleus activation in health and disease. For example, it has been previously reported that DNIC expression is abolished in rodent models of chronic pain 4,38,54,18 , highlighting the vital role that endogenous pain modulatory pathways including DNIC play in nociceptive processing/pain.…”
Section: Discussionmentioning
confidence: 99%